(untitled) (Journal of the College of Basic Education, 2025)
In response to rising water shortages and the growing need for sustainable agriculture methods, this study describes the creation of a smart environmental monitoring and automated irrigation system based on Arduino technology, The system uses a number of sensors, including a soil moisture sensor, a DHT11 temperature and humidity sensor, a rain sensor, and a water level sensor, to monitor environmental conditions in real time. Sensor data are shown on an LCD screen and on the Serial Monitor for debugging and monitoring. A relay-controlled water pump is started based on certain conditions, such as dry soil, no rain observed, and a sufficient reservoir water level. Arduino IDE is used for programming, and Tinkercad for simulation and testing before physical implementation, which enhances the development process and reduces errors. The proposed system improves water management, decreases manual intervention, and promotes sustainable agriculture. The suggested approach is low-cost, flexible, and scalable, making it appropriate for small-sized agricultural applications, as well as for both educational and practical agricultural applications. The findings show that smart irrigation not only conserves resources but also improves farming production efficiency.